THE (IN)EFFICIENCY IN THE ENFORCEMENT OF THE 2017 MIGRATION LAW AND THE CONTEXT OF VENEZUELAN MIGRATION IN BRAZILIAN TERRITORY - Pacheco Silva, Laís Helena; Ramos Perez Martins, Karina; dos Santos Ramos Souza, Juliane (Revista Gênero e Interdisciplinaridade, 2021)
The present work expose an analysis of the historical context of migrations in the geographical space, and the evolution of this phenomenon in contemporary times, from the influence of world geopolitical conflicts. Thus, it was identified the clear incongruity of the conceptualization of immigrants carried out by the United Nations (UN) - from the need for cross-border mobility by international conflicts, natural disasters and own will- to safeguard their fundamental rights, even if there are tools in the Brazilian legal system. In addition, this research addresses the Venezuelan migratory crisis that is plaguing the country's territory and has repercussions on the Brazil-Venezuela borders, especially the state of Roraima, as a factor of modification of the geographical and geopolitical space of both nations. Thus, it is appropriate to assimilate the consequences and the impacts on the Brazilian State, which impacted on the inability to apply Migration Law nº 13,445, of May 24, 2017. The use of the new Law sought to safeguard the fundamental rights of immigrants and preserve the interests of the Brazilian people, providing stability and social order. However, at the end of the survey, the 2017 Migration Law was ineffective in terms of protecting the individual rights of Venezuelans in the country and safeguarding their dignity, as their provisions didn’t achieve the expected efficiency in containing hate speech, violent practices by the Brazilian people, and even xenophobia practiced by the state judiciary itself. The methodology employed in the present work consists of a bibliographic research of the case study, using articles 1º, 2º, 3º and 4º of the Law nº 13.445, of May 2017 and the Constitution of the Federative Republic of Brazil of 1988, in addition to the Universal Declaration of Human Rights, using the analysis of scientific articles, specific reports and newsletters from the official UN website